Municipal Management and Local Governance : A Service Delivery Perspective - World Bank (World Bank, Washington, DC, 2014)
The Norwegian Social Science Research Institute (FAFO) in conjunction with field based teams in five Middle East and North Africa (MNA) region countries worked under the guidance of the World Bank to organize, design and implement a Service Delivery Survey (SDS) spanning the period 2005-61. The SDS diagnostic examines the linkages between government policies and service delivery performance. The aim of the exercise was to provide an end-user perspective on potential ways of improving service quality, cost and outreach outcomes. It builds upon the institutional and policy review carried out in the MNA-8 countries by the World Bank in 2004 and uses the body of knowledge generated as a basis for refining the service delivery analysis in several ways. First, by surveying end-users it assesses their perception of the quality and coverage of services, improvements that they have noted, and the deficiencies that still exist. Second, it gauges their understanding of the service delivery mechanism, i.e. whether the users feel private sector providers, local governments, central government agencies or other providers are the preferred provider; if so, why; and whether there are general principles that can be derived from the user feedback. Third, it also considers the costs of provision under alternative arrangements, efficiency gains and inherent subsidies or losses that could be potentially averted under alternative institutional arrangements. Two methodologies were employed; focus group discussions complemented by Transect surveys, which, together, provide a window to the overall nature of service delivery in the selected Middle East countries. Certain central themes and concerns cutting across different services and countries emerge from these discussions. These are highlighted below. However, it should be noted that the purpose of implementing the SDS was not to generate definitive policy recommendations for each country. Samples sizes of cities (two per country) and within city (100 transect questionnaires and approximately 45 focus group discussion participants) hardly constitute a representative sample. Rather, the purpose of the SDS was to expose central government officials and city-level representatives and staff to cost-effective tools and techniques in consulting their constituents on key service delivery issues.